Board Characteristics And Cybersecurity Disclosure In The Indonesian Banking Industry - Dalimunthe, Nurul Amalina; Sari, Vita Fitria (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to examine the effect of board characteristics on Cybersecurity Disclosure (CSD), including the number of board members, board meetings, gender diversity of the board of directors, the number of commissioners, gender diversity of the board of commissioners. Profitability, company size, and leverage are used as control variables. The research subjects include banking sector companies listed on the Indonesia Stock Exchange from 2020 to 2024 using a total sampling approach, resulting in 235 samples. Data analysis applied multiple linear regression analysis. The research findings show that the number of board members, the number of commissioners, and the gender diversity of commissioners have an effect on Cybersecurity Disclosure (CSD). Meanwhile, board of directors meetings and gender diversity on the board of directors do not affect Cybersecurity Disclosure (CSD). These findings explain that companies with larger boards, as well as the presence of more female directors on the board of commissioners, encourage cybersecurity transparency. Keywords: Number of Board of Directors; Board of Directors Meetings; Gender Diversity of the Board of Directors; Number of Board of Commissioners; Gender Diversity of the Board of Commissioners